The Literary Experience of God in Death’s Vicinity in the Works of Freedom Fighter Bronius Krivickas - Čiočytė, Dalia (Literatūra, 2020)
Bronius Krivickas (1919–1952), a Lithuanian poet and fiction writer, a fighter against the Soviet occupation of Lithuania, reflects carefully the main ideas of existentialism: Søren Kierkegaard’s concept of individual freedom, Martin Heidegger’s notion of being-toward-death, the concept of a limiting situation developed by Karl Jaspers. In the worldview of B. Krivickas’s literary works, these ideas are associated with the context of Catholic philosophy and theology.This article investigates the notion of God within the existential limiting situation (especially the situation of death) in the literary works by B. Krivickas. The main critical perspective is the theology of literature.In the context of the dramatic experience of World War II, B. Krivickas’s short stories, a symbolist play A Tale About a Princess, and poetical prose works interpret God as being perceived through human conscience and a human longing for spiritual harmony. God is being thought of as the ultimate metaphysical mystery.In the period of Lithuanian fights for freedom, B. Krivickas’s poetry reveals an intense partisan self-consciousness. The poetry interprets the fight against the Soviet aggressor as a sacrifice for the nation’s freedom and compares it indirectly with the ultimate sacrifice of Jesus Christ. According to the logic of existentialism, B Krivickas’s poetry claims that a human being is absolutely free, even if this means to choose freedom at the cost of life.God becomes the personal you for the fighter seen in B. Krivickas’s poetry. The main theme of the fighter’s dialogue with God is an existential complaint. The fighter experiences deep theodic dilemmas. He has no doubts about the righteousness of the war against the Soviet occupation, but he has deep doubts about the divine permission for evil to exist in the world. The faith of the poetic fighter is just his will to believe, his desire to believe. Thus the poetic figure of the fighter acquires both patriotic and religious heroism.
Keywords: the theology of literature; a limit existential experience; theodicy; the metaphor of the severe God